Anti-Inflammatory Property of the Ethanol Extract of the Root and Rhizome of Pogostemon cablin (Blanco) Benth - Chu-Wen Li; Xiao-Li Wu; Xiao-Ning Zhao; Zu-Qing Su; Hai-Ming Chen; Xiu-Fen Wang; Xiao-Jun Zhang; Hui-Fang Zeng; Jian-Nan Chen; Yu-Cui Li; Zi-Ren Su (The Scientific World Journal)
The aim of this study was to investigate the anti-inflammatory property of the ethanol extract of the root and rhizome of Pogostemon cablin (ERP). The anti-inflammatory effect was evaluated using four animal models including xylene-induced mouse ear edema, acetic acid-induced mouse vascular permeability, carrageenan-induced mouse pleurisy, and carrageenan-induced mouse hind paw edema. Results indicated that oral administration of ERP (120, 240, and 480 mg/kg) significantly attenuated xylene-induced ear edema, decreased acetic acid-induced capillary permeability, inhibited carrageenan-induced neutrophils recruitment, and reduced carrageenan-induced paw edema, in a dose-dependent manner. Histopathologically, ERP (480 mg/kg) abated inflammatory response of the edema paw. Preliminary mechanism studies demonstrated that ERP decreased the level of MPO and MDA, increased the activities of anti-oxidant enzymes (SOD, GPx, and GRd), attenuated the productions of TNF-α, IL-1β, IL-6, PGE2 and NO, and suppressed the activities of COX-2 and iNOS. This work demonstrates that ERP has considerable anti-inflammatory potential, which provided experimental evidences for the traditional application of the root and rhizome of Pogostemon cablin in inflammatory diseases.